Modeling and Simulation Analysis of Power Dispatch of Solar Photovoltaic Microgrid in Paper Mill - Ying Gao; Yusha Hu; Jigeng Li; Mengna Hong; Yi Man (Chemical Engineering Transactions, 2020)
With the depletion of fossil energy, it becomes more and more urgent to find alternative energy sources. Renewable energy plays an important role in energy structure transition. The change of energy structure has challenged the operation of traditional power systems to a great extent. Emission load dispatch problem is one of fundamental issues of power system operation. It is a complex issue to reduce the time for power dispatch as short as possible in different time intervals and conditions. According to the characteristics of supply-side operation and dispatch in paper mill as well as the historical and simulation data, a dispatch model was developed based on the Generative Adversarial Nets (GAN) algorithm to solve the energy storage scheduling issue for solar photovoltaic microgrid. Industrial data was used to verify the proposed model. Compared with GA method and DQN method, the GAN method was able to reduce the operating costs by 3.639 % and 2.734 %. The results show that the model can effectively decrease the operation cost.